NEOKOLONIALISME EKOLOGIS DALAM NOVEL BATU BERKAKI: KAJIAN EKOKRITIK - Sampurno, Nailil Haliza; Wardani, Rr Elisabeth Nugraheni Eko; Suryanto, Edy (Universitas Hamzanwadi, 2025)
This study aims to examine the novel Batu Berkaki through an ecocritical approach by highlighting the practice of ecological neocolonialism within the scope of village society. The main focus of this study is: (1) capitalism and power over natural resources, (2) the representation of nature as a space of conflict and exploitation, and (3) ecological memory and trauma. This research method is an ecocritical analysis method with an ethical study model. The data in this study are in the form of quotations contained in the novel Batu Berkaki. The results of this study indicate that the novel Batu Berkaki represents neocolonialism framed through the practice of capitalism. Neocolonialism is shown through the behavior of the Munarto family towards the residents of Ledok Awu Village, while environmental ethics are reflected by the character of Mbok Im, namely responsibility and morals towards nature. This study shows that nature becomes an active subject in the struggle for power as well as a victim of human possession driven by capitalist ideology.